The Development of Picture Story Book to Improve the Science Literacy Skills of Grade 4 Elementary School Student - Uzlifatul Rusydiana; Wahono Widodo; Nadi Suprapto (Indonesia Approach Education, 2023)
Scientific literacy can be interpreted as a person's ability to study science and then implement it in everyday life so that he is able to act wisely as a person or as a social being. This study aims to produce a picture story book learning tool that is valid, practical, and effective to improve the science literacy skills of 4th grade elementary school students. The research method used is R&D with a static-group pretest-posttest design. The sample is grade 4 students with 30 students as the control and 30 students as the experimental class. The data were collected by using validation, observation, questionnaire, and test sheets. The results showed that the scientific literacy test results had increased. The mean pretest score for the control class was 55.1 and posttest score for the control class was 67.4. The average pretest score for the experimental class was 59.07 and posttest score for the experimental class was 86.8. The N-Gain mean for the control class was 0.27 and 0.70 for the experimental class in the medium category. It can be concluded that the picture story book and supporting tools are valid, practical, effective, and can be used to train the scientific literacy skills.